Differences in pacing during cycling and running in ultra-triathlons - The example of `Swissultra` - Weiss, K.; Sousa, C.V.; Thuany, M.; Cuk, I.; Nikolaidis, P.T.; Knechtle, B. (European Review for Medical and Pharmacological Sciences, 2022)
OBJECTIVE: The knowledge of the most predictive split discipline and the pacing during a triathlon race is of utmost importance for planning an ultra-triathlon race. This study aimed at investigating the pacing during cycling and running splits in three different multi-stage ultra-triathlon race formats (i.e., Quintuple, Deca, and Double Deca Iron ultra-triathlon with 5x, 10x and 20x the daily distance of a full Ironman-distance triathlon).